(untitled) (Fiep Bulletin - online, 2014)
Objective: Checking the changes in the Arterial Pressure, Heart Frequency, Rate of Body Mass and Rate of Waist and Hip in a non-monitored program. Methods: This study was done in Itajaí, a city in south of Brazil, between April and July 2007 completing 8 (eight) weeks of training aiming for the observation of the evolution of the participants who were really committed in this program during the mentioned period. Results: The general characteristics of the group are shown in Table 1. Significant differences in the anthropometric changing weren’t found, as the arterial diastolic and systolic pressure, Heart Frequency of resting and double product. Conclusion: The effect of this non-monitored walk in elder women didn’t show any changing in the analyzed parameters, however, the most effective way to slow down the impacts of cardiovascular illnesses as arterial hypertension is by actions in populational level and individual level focused on the development of preventing and treatment actions. Although when it is dealt with community programs, it still remains the difficulty of controlling the intensity and amount of exercise and this makes more difficult the clinical evaluation of the results in this kind of program. In this study we did not get significant results in the analyzed changes, in this way it is worth to assure the necessity of new researches with the objective of proving if programs of non-monitored walking present a more positive result in a longer term.